Development of a retrospective process for analyzing results of a HMM based posture recognition system in a functionalized nursing bed - Demmer Julia; Kitzig Andreas; Naroska Edwin (Current Directions in Biomedical Engineering, 2017)
In the area of care in general but especially in the care of elderly, there is a great interest in deriving patient parameters preparation free. For this purpose, a load cell functionalized nursing bed has been developed at Niederrhein University of Applied Science. The system allows analysis and recognition of the persons’ positions and actions in the bed. The Hidden Markov Toolkit (HTK) based posture recognition system was initially presented at the BMT 2015 by our research group. The initial system shows good results but to draw conclusions about the patient's condition, a minimum possible error rate should be achieved. For this purpose, a two-step retrospective analysis of the initial results was developed as an extension to improve the accuracy of the system.